PENGARUH MODAL INTELEKTUAL TERHADAP KINERJA BISNIS BANK UMUM SYARIAH (BUS) DI INDONESIA - Nanda Harianto; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2013)
The purpose of this study was to determine the effect of intellectual capital on the business performance of Sharia Commercial Banks in Indonesia. Dependent variable used in this study is the financial performance of Sharia Commercial Banks based on islamicity financial performance index. Independent variables used in this study is the intellectual capital which is measured by using Pulic model that called Value Added Intellectual Coefficient (VAIC). The sample in this study is the Sharia Commercial Banks registered in Bank Indonesia in 2008-2011. The sample was selected using purposive sampling method and obtained eleven banks being sampled. Pulic model (Value Added Intellectual Coefficient) was used as a measure of the efficiency of components of intellectual capital: physical capital coefficient (VACA), human capital coefficient (VAHU), and structural capital coefficient (STVA). This study used partial least squares to analyze the data.The results showed that the intellectual capital significantly effect on Business Performance Sharia Commercial Banks and can be used to predict future Business Performance Sharia Commercial Banks. In addition the average growth of intellectual capital (ROGIC) also significantly influence future Business Performance Sharia Commercial Banks.